Permainan Warna Berpengaruh Terhadap Kreativitas Anak Usia Dini - Aisyah Aisyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
The world is full of colors, and the kids love the bright colors. When pre-school age, they also like to use bright colors like red, yellow, blue, or rainbow colors (mejikuhibiniu). Though in this world there are not only these colors, but hundreds or thousands of colors. So when they use crayons that amount to 12 colors, that look only limited to existing colors. They know less or may not even know that from the 12 existing colors they can get other new colors. This study aims to prove that the color game given to Kindergarten students can improve the creativity of children in coloring the image. Early. The benefits of this research is expected to contribute in order to understand the existence of color game activities in improving the creativity of children Early Age. Data collection by check list and observation techniques, and processed in a nonstatistik way or can also be referred to as a simple statistical analysis by finding percentages. The results show that color games are significant to influencing the creativity of young children.